2014
DOI: 10.1155/2014/853572
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Thermally Treated Chitosans and Chitosans Obtained by Alkaline Deacetylation

Abstract: The thermal depolymerization of chitosan and alkaline deacetylation of chitin were characterized by measurement of viscosity, gel permeation chromatography (GPC), potentiometric titration (PT), and proton nuclear magnetic resonance spectroscopy (H1NMR). The depolymerization rates (DR) measured by kinematic viscosity (KV), apparent viscosity (AV), and GPC (Mw) until 4 h of treatment wereDRKV=21.9,DRAV=25.5, andDRMw=23.3% h-1and for 5 to 10 h of treatment they decreased slowly to produce ofDRKV=0.545,DRAV=0.248,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
3
0
2
Order By: Relevance
“…Oliveira et al [18] comparando os resultados de GA obtidos por titulação potenciométrica e por RMN 1 H (ressonância magnética nuclear de próton) observaram que não houve diferença entre estes métodos para quitosana com GA que variaram entre 8 e 22%. Desta maneira, o método de titulação potenciométrica mostra-se um método simples, barato e bastante confiável na determinação do GA de quitosana, desde que se tomem os cuidados anteriormente citados.…”
Section: Massa Molar E Grau De Acetilaçãounclassified
“…Oliveira et al [18] comparando os resultados de GA obtidos por titulação potenciométrica e por RMN 1 H (ressonância magnética nuclear de próton) observaram que não houve diferença entre estes métodos para quitosana com GA que variaram entre 8 e 22%. Desta maneira, o método de titulação potenciométrica mostra-se um método simples, barato e bastante confiável na determinação do GA de quitosana, desde que se tomem os cuidados anteriormente citados.…”
Section: Massa Molar E Grau De Acetilaçãounclassified
“…For example, the Mw of Acheta domesticus measured by different studies varies widely from 86.8-344 kDa [56,59]. Various methods have been developed to measure the Mw of chitosan, including gel permeation chromatography, size exclusion chromatography, and viscometry [125,126]. Leke et al revealed that chitosan samples from black soldier fly (Hermetia illucens) meal, extracted by three different sources-enzyme-, microwave-, and ultrasound-assisted methods-displayed both antioxidant and antimicrobial activity.…”
Section: Molecular Weightmentioning
confidence: 99%
“…Este grau também está relacionado com a solubilidade da quitosana, em meios de acidez moderada, pois seu valor expressa a quantidade de grupos amino disponíveis para protonação e que geram cargas (-NH 3 + ) na cadeia polimérica. Quanto menor o valor do GA, maior a quantidade de cargas presentes na cadeia e mais importante é a repulsão eletrostática entre elas, consequentemente, maior será a solubilidade da quitosana [20,21] . Desta forma, a massa molar e o GA obtidos para a quitosana, neste estudo, são inferiores aos observados pelos autores supracitados, o sugere que esta apresenta melhor solubilidade, em soluções de acidez moderada.…”
Section: Viscosidade Massa Molar Grau De Acetilação E Análise Elemeunclassified